Fault diagnostic advisory system using moving-range chart and hazard operability study - Heng, Han Yann; Ali, Mohamed Wijayanuddin; Kamsah, Mohd. Zaki (Faculty of Chemical and Natural Resources Engineering, UTM, 2007)
In this paper, fault diagnostic advisory system developed by using the combination of Univariate Statistical Process Control (SPC) and Hazard and Operability (HAZOP) study supported by rule-based approach is presented. Firstly, a plant model was simulated by using commercial HYSYS. PlantTM simulator. Moving-Range (x-MR) Chart and HAZOP study were used to define the causes and consequences of process deviation based on selected parameter for each study node. Fault is considered to occur if one variable is out of control limit. The advisory system has successfully detected and diagnosed the deviations and displayed the causes and consequences of the faults. Although the scheme was developed based on precut fractionation column, the algorithm of fault detection and diagnosis can be extended to other chemical process by changing the x-MR chart and HAZOP study for each selected monitoring variables